Disseminating information through social media during Covid-19 pandemic among university students - Pricilla Uran,; Shazleen Mohamed,; Ahlam Abdul Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The current rate of technological innovation makes it easier to convey data from one person to another. As technology progresses, it becomes easier for everyone to access social media, to the point where some news organisations seek to exploit it as a news source. Meanwhile, in order to avoid public panic, it is critical to educate society at a young age about the impact of fake news on social media. The purpose of this study is to explain the purpose of social media usage and to investigate whether the use of social media platforms to disseminate information has increased the spread of fake news in Malaysia, as well as the effect of information disseminated among university students during the COVID pandemic. Social media is well-known for its ease of use, particularly among young people, in sharing and expressing their opinions on domestic and international topics. Using social media has become second nature to us, particularly during the COVID-19 pandemic. Because of the strength of social media, the public's opinion of finding information during a lockdown is quite positive. The study was carried out in a qualitative manner. The researcher gathered all of the data by asking the participants general research questions. The method employed to obtain the results was an in-depth interview. The findings revealed that information disseminated via social media was successful in raising awareness during the pandemic, particularly among university students. According to the findings, certain scientific and technical advancements should benefit the global community rather than be manipulated in order to obtain accurate and true knowledge; society must be astute. False knowledge would have negative repercussions, and society would inevitably exist in a state of deception. Obtaining reliable information during the COVID-19 pandemic is critical to ensuring that individuals become social media literate in the future.